La desintegración familiar y su relación con el desarrollo cognitivo de los niños y niñas de primero de educación básica de la unidad educativa “Pedro Bouguer” de la parroquia Yaruquí, cantón Quito, provincia de Pichincha. periodo lectivo 2013-2014 - Vallejo Aguirre, Carolina Elizabeth (2016)
This thesis refers to "FAMILY APART AND ITS RELATION TO COGNITIVE DEVELOPMENT OF CHILDREN OF FIRST BASIC EDUCATION UNIT" PEDRO BOUGUER "PARISH YARUQUI, CANTON QUITO, PICHINCHA PROVINCE. PERIOD 2013-2014". In the first year of Basic Education in "Pedro Bouguer" Unit of the parish Yaruqui, identified 30% of dysfunctional homes; these causes affect the child and as a result the process of knowledge acquisition significant, because an imbalance in the interrelations family, alters the other social structures and cognitive, by this reason the stated goal with the development of this research is: Determine how family breakdown affects cognitive development of children of Basic Education First Educational Unit "Pierre Bouguer" the Yaruquí parish, Canton Quito, Pichincha for the academic year 2013-2014, in order to establish measures to minimize this involvement. In the development of research have applied the following methods: observation to understand the functioning and structure of the synthetic, analytical to process all the information gathered, educational unit to establish the specific ideas in each chapter project for deductive establish how family breakdown affects cognitive development, and inductive for the findings and propose mitigation actions. The applied study found that 27.86% of the families of the children in the first year Basic Education Educational Unit "Pierre Bouguer" dysfunctional, which states that there is a strong need. Family APGAR questionnaire is concluded that 27.86% of households in the first year Basic Education Educational Unit "Pierre Bouguer"; by testing cognitive skills is evidence that children who come from dysfunctional families have more cognitive deficiencies than those from normotensive families function skills; by cognitive diagnostic questionnaire evidence that children who come from dysfunctional families always or sometimes have a higher incidence of cognitive problems than those who come from families norm functions. For these reasons, it is justified to implement strategies to minimize the existing problems, and help improve cognitive development in children of Basic Education First Educational Unit "Pierre Bouguer" whose families have problems of family disintegration.